Efficient Oxidation with Singlet Oxygen from 5,10,15,20-Tetraphenylporphyrin under Blue LED Irradiation and Air Atmosphere: Simplified Preparation of Key Building Blocks for Natural Product Synthesis - Hasumi, Masato; Tsutsumi, Tomohiro; Shikama, Daiki; Hayakawa, Ichiro (Synthesis, 2024)
A method for preparing important building blocks for natural product synthesis has been developed using singlet oxygen generated from 5,10,15,20-tetraphenylporphyrin under blue LED irradiation. Using this method, the allylic oxidation of dicyclopentadiene proceeded smoothly in air atmosphere with an 87% yield. The conditions, using TPP under blue LED irradiation, were expanded to include the oxidation of cyclopentadiene. The approach offers a simple and cost-effective method of synthesizing important building blocks for natural product synthesis.
Keywords: 5,10,15,20-tetraphenylporphyrin; blue LED; air atmosphere; singlet oxygen; dicyclopentadiene; cyclopentadiene